(3CSeGA LHGd JgGeIs - (3YQGe Hf GdGUHYs
(3ChdgG (B:s
(3bGd YQGe Hf GdGUHY GdSdei bGd GSeGA LHGd JgGeg heG ajgG ef GdbQi heG jfHJ YdjgG ef GdGTLGQ heG ajgG ef GdejGg ChdgG QVhi s
(3BNQgG (B:s
(3hdG Yde GdG eG cGf ef GdGfUGH GdJi cGfJ ai GdLGgdjI hGf JNHQhfG MGd QcHg GLeYG Je cJGH GeSGA LHGd ecI hGdeOjfI heG jJUd HgG HMeO Gdgd hYhfg hMSf JhajbI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdSYjOjI HMjOQ CHGO (B((3MOjK (B355) s
Keywords: (3GdLZQGajG h GdHdOGfs